Method for producing zeolite

The method addresses the challenge of producing high-purity and high-crystallinity zeolite on a large scale by using a stirred tank reactor with controlled mixing and aging, achieving uniformity and purity through specific stirring conditions and agent addition.

JP2025010070APending Publication Date: 2025-01-20MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024106360
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-07-01
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for producing zeolite on a large scale face challenges in achieving uniform mixing of raw materials, leading to decreased crystallinity and contamination by by-products, making it difficult to obtain high-purity and high-crystallinity zeolite.

Method used

A manufacturing method involving a stirred tank reactor with a stirring blade speed of 5 m/s or more, a mixing time of 30 seconds to 900 seconds, and controlled addition of raw materials, including an organic structure directing agent, to prepare a uniform aqueous reactant precursor.

Benefits of technology

This method enables the production of high-purity and highly crystalline zeolite in large quantities by ensuring uniform mixing and controlled aging and hydrothermal synthesis, reducing the need for long mixing times and minimizing by-product formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010070000013
    Figure 2025010070000013
  • Figure 2025010070000014
    Figure 2025010070000014
  • Figure 2025010070000015
    Figure 2025010070000015
Patent Text Reader

Abstract

To provide a production method for obtaining zeolite having high purity, and high crystallinity by preparing a uniform raw material aqueous reaction product precursor in a stirred vessel-type reactor for a short time, aging, and subjecting to hydrothermal synthesis.SOLUTION: A method for producing zeolite includes: a mixing process of mixing at least a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reaction product precursor; an aging process of aging after the mixing process; and a hydrothermal synthesis process, where the aqueous reaction product precursor is mixed using a stirred vessel having a volume of 10 liter or more, and a stirring blade in a mixing process, and the average blade end peripheral speed is 5 m / s or more in the mixing process.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a zeolite, and more particularly to the production, aging, and production of an aqueous reactant precursor of a zeolite using a large-scale (e.g., 10 L or more, more preferably 500 L or less) stirred tank. [Background technology]

[0002] Zeolites have properties such as a molecular sieve effect, ion exchange ability, catalytic ability, and adsorption ability due to the pores derived from their framework structure, and are currently widely used as adsorbents, ion exchange agents, industrial catalysts, and environmental catalysts.

[0003] In mass-scale production of zeolite, raw materials are generally added successively to a stirred tank reactor, an aqueous reactant precursor is prepared, aged, and then hydrothermal synthesis is performed. On the other hand, it is known that it is difficult to realize uniform mixing of raw materials depending on the composition of the aqueous reactant precursor. If aging and hydrothermal synthesis are performed in the state of the non-uniform aqueous reactant precursor, the crystal growth rate is affected, and as a result, the desired high-purity and high-crystalline zeolite cannot be obtained. For example, in Patent Document 1, AEI zeolite, which is considered to be particularly difficult to mass-produce, is produced in 0.1 liter units. In Patent Documents 2 and 3, etc., production is performed at the 1 liter level to obtain several hundred grams of AEI zeolite. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-81809 A [Patent Document 2] JP 2017-206417 A [Patent Document 3] JP 2021-147260 A Summary of the Invention [Problem to be solved by the invention]

[0005] According to the techniques disclosed in the above-mentioned Patent Documents 1 to 3, it is possible to produce a maximum of several hundred grams of zeolite. However, when producing a larger amount of zeolite, specifically, when using a stirring tank of 10 liters or more, there is a problem that the characteristics deteriorate due to a decrease in crystallinity and by-products other than the desired zeolite are mixed in, making it impossible to produce a large amount of good quality zeolite. In addition, when preparing a large amount of aqueous reactant precursor of a normal zeolite, it is mainstream to use a stirred tank type reactor. However, it is known that it is difficult to achieve uniform mixing in a short time depending on the physical properties of the prepared aqueous reactant precursor. In response to this, for example, when preparing a raw material aqueous reactant precursor having high viscosity, the order of addition of the zeolite synthesis raw materials, that is, the Si element source, Al element source, alkali metal element source, organic structure directing agent added as necessary, and water, and further the addition rate of the raw materials are usually controlled. However, in order to achieve a relatively uniform mixed state of the aqueous reactant precursor, a long mixing time (several hours to several tens of hours) was required. Furthermore, although it is a preferable embodiment to prepare the aqueous reactant precursor, age it, and synthesize it hydrothermally in the same stirred tank type reactor, a stirring system suitable for the physical properties of the aqueous reactant precursor and the gelation of the raw materials during hydrothermal synthesis has not been established. As a result, the aqueous reactant precursor becomes non-uniform, and there is a problem that the target zeolite with high purity and high crystallinity cannot be obtained.

[0006] Therefore, an object of the present invention is to provide a production method for obtaining a large amount of a high-purity, highly crystalline zeolite by preparing a uniform aqueous reactant precursor in a short time and aging and hydrothermal synthesis. In a more preferred embodiment, the present invention is to provide a production method for obtaining a large amount of such a high-purity, highly crystalline zeolite in a stirred tank reactor. [Means for solving the problem]

[0007] As a result of extensive investigation into the above-mentioned problems, the inventors have discovered that when producing an aqueous reactant precursor using a stirring tank of 10 L or more in the mixing step, it is important that the peripheral speed of the stirring blade is a certain speed or higher, and have arrived at the present invention.

[0008] That is, the gist of the present invention is as follows. [1] A method for producing a zeolite, comprising: a mixing step of mixing at least a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; an aging step of aging the mixture after the mixing step; and a hydrothermal synthesis step, A method for producing a zeolite, wherein in the mixing step, the aqueous reactant precursor is mixed using a stirring tank of 10 liters or more and a stirring blade, and the average peripheral speed of the blade tip in the mixing step is 5 m / s or more. [2] The method for producing a zeolite according to the above [1], wherein the total time during which the blade tip peripheral speed is 10 m / s or higher is 30 s or more and 900 s or less. [3] The method for producing a zeolite according to the above [1] or [2], wherein an organic structure-directing agent is added at least in any one of the stages of the mixing step, the aging step, between the mixing step and the aging step, and after the aging step and before the hydrothermal synthesis step. [4] The method for producing a zeolite according to any one of the above [1] to [3], wherein the mixing step, the aging step, and the hydrothermal synthesis step are carried out in a stirred tank reactor. [5] The framework density of the zeolite is 14T / 1000Å. 3 Over 19T / 1000Å 3 A method for producing a zeolite according to any one of the above items [1] to [4], which is as follows: [6] The method for producing a zeolite according to any one of the above [1] to [5], wherein the zeolite has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. [7] The method for producing a zeolite according to any one of the above [1] to [6], wherein the ratio of Si element to Al element in the aqueous reactant precursor is, in terms of the molar ratio of the oxide of Si element to the oxide of Al element (SiO2 / Al2O3 molar ratio), 5 or more and 1,000 or less. [8] The ratio of Si element to alkali metal element contained in the aqueous reactant precursor is M to oxide of Si element. (2 / n) O (M is an alkali metal element, and n is 1) molar ratio (M (2 / n) The method for producing a zeolite according to any one of the above [1] to [7], wherein the zeolite has a molecular weight of 0.01 or more and a molecular weight of 0.5 or less. [9] The method for producing a zeolite according to any one of the above [1] to [8], wherein an alkaline earth metal element source is further mixed in the mixing step.

[10] The ratio of silicon to alkali metal and alkaline earth metal elements contained in the aqueous reactant precursor is M to oxide of silicon. (2 / n) The molar ratio (M (2 / n) The method for producing a zeolite according to the above [9], wherein the zeolite has a molecular weight of 0.02 or more and a molecular weight of 0.5 or less.

[11] The method for producing a zeolite according to any one of the above [1] to

[10] , wherein the alkali metal element source contains at least a potassium element source.

[12] The method for producing a zeolite according to the above

[11] , wherein a molar ratio of potassium element to alkali metal element contained in the alkali metal element source in the aqueous reaction mixture is 0.01 or more and 1 or less. Effect of the Invention

[0009] According to the present invention, a manufacturing method can be provided for preparing a uniform aqueous reactant precursor in a stirring tank in a short period of time, and then maturing and hydrothermally synthesizing the precursor to obtain a large amount of high-purity, highly crystalline zeolite. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of a typical stirred tank reactor used in the present invention. [Diagram 2]XRD patterns of representative target AEI-type zeolite, impurity MOR-type zeolite, impurity GME-type zeolite, impurity MER-type zeolite, impurity ANA-type zeolite, and impurity sanidine (mineral, AlSi3O8). [Diagram 3] XRD charts of the zeolites produced in Reference Example 2, Example 3, Comparative Example 1, and Comparative Example 2 of the present invention. [Figure 4] XRD chart of the zeolite produced in Example 1 of the present invention.

Embodiments for Carrying Out the Invention

[0011] Hereinafter, embodiments of the present invention will be described in detail. However, the following description is an example of the embodiments of the present invention, and the present invention is not limited to these contents in any way. Also, the embodiments of the present invention can be combined as appropriate. In this specification, "~" means a range including the numerical values described before and after it.

[0012] [Method for Producing Zeolite] The method for producing the zeolite of the present invention includes a mixing step of mixing at least a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor, an aging step of aging after the mixing step, and a hydrothermal synthesis step. In the mixing step, the aqueous reactant precursor is mixed using a stirring tank of 10 liters or more, preferably 20 liters or more, and a stirring blade, and the average peripheral speed of the blade tip is 5 m / s or more in the mixing step. In the present invention, the mixture obtained by the above mixing step is referred to as an aqueous reactant precursor. However, the raw materials before the hydrothermal synthesis step, which are obtained through the aqueous reactant precursor and the subsequent aging step, may be described as "zeolite synthesis raw materials" or "gel mixture".

[0013] Hereinafter, the raw materials used in the production method of the present invention will be described in more detail. [Si Element Source] The Si element source is a compound having Si atoms (hereinafter sometimes referred to as "Si compound" or "Si element raw material"). In the hydrothermal synthesis step, an amorphous Si compound is preferred because it is considered to be easily dissolved so as to have an Si / Al ratio suitable for the crystallization of zeolite. Examples of the amorphous Si compound include amorphous silica such as colloidal silica, amorphous silica, fumed silica, and sodium silicate; trimethylethoxysilane, tetraethyl orthosilicate, aluminosilicate gel, etc. These may be used alone or in combination of two or more in any ratio. Also, from the viewpoint of being easily mixed uniformly with other raw materials and being easily dissolved in water, colloidal silica, trimethylethoxysilane, tetraethyl orthosilicate, and aluminosilicate gel are preferred. Among the above-described Si element raw materials, colloidal silica is particularly preferred.

[0014] <Al element source> The Al element source is a compound containing Al atoms (hereinafter sometimes referred to as "Al compound" or "Al element raw material"). As the Al compound, a compound that is easily dissolved in water is preferred. Also, a compound that is miscible with the Si compound and is easily dissolved so as to have an Si / Al ratio suitable for the crystallization of zeolite in the aging step and the hydrothermal synthesis step is preferred. From the above viewpoints, as the Al compound, amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide, etc. are preferred. These may be used alone or in combination of two or more in any ratio. Among these, particularly preferred are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure. As the Al compound, it is preferable to use an amorphous aluminum element raw material, and among the above, amorphous aluminum hydroxide is particularly preferred.

[0015] (Amount of Al element source added) The Al element raw material is preferably used such that the ratio of the Si element source to the Al element source relative to the total amount of Al atoms in the aqueous reaction mixture before hydrothermal synthesis, in terms of the molar ratio of the oxide of the Si element source to the oxide of the Al element source (molar ratio of SiO2 / Al2O3), is 5 or more and 1000 or less. By setting the Si / Al molar ratio in the above-mentioned range, the target zeolite can be easily obtained. From the above viewpoints, the SiO2 / Al2O3 molar ratio is preferably in the range of 5 or more and 1000 or less, more preferably in the range of 7 or more and 500 or less, even more preferably in the range of 8 or more and 100 or less, and particularly preferably in the range of 10 or more and 30 or less.

[0016] <Alkaline metal element source> The alkali metal element source is not particularly limited, and may be a compound containing an alkali metal atom, and preferably, an alkali metal ion is contained in the aqueous reactant precursor before hydrothermal synthesis. As the alkali metal element source, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, and organic acid salts such as acetates, oxalates, and citrates of the above-mentioned alkali metal atoms can be used. The alkali metal element source may be used alone or in any combination of two or more kinds in any ratio. As the alkali metal element, known alkali metal elements used in the synthesis of zeolites can be used. Specifically, at least one selected from lithium, sodium, potassium, rubidium, and cesium is preferable. By including these alkali metal elements, the crystallization of zeolites can be easily promoted, and the amount of expensive OSDA added can be reduced. Among the above alkali metal elements, sodium and potassium are particularly preferred, and it is preferable to contain at least a potassium element source. The alkali metal elements may be used alone or in combination of two or more.

[0017] (mixed amount of alkali metal elements) The ratio of Si element to alkali metal element contained in the aqueous reactant precursor (gel mixture) before hydrothermal synthesis is M to oxide of Si element. (2 / n) O (M is an alkali metal element, and n is 1) molar ratio (M (2 / n) The molar ratio of the alkali metal oxide to the oxide of the Si element (M O / SiO2) is preferably 0.01 or more and 0.5 or less. When the ratio is within this range, the target zeolite is easily obtained. From the above viewpoints, the ratio of the oxide of the alkali metal element to the oxide of the Si element (M (2 / n) The molar ratio of the alkali metal element to the Al atom contained in the aqueous reactant precursor is preferably 0.8 to 1.2. In addition, when several kinds of alkali metal elements are mixed, a mixture of sodium element and potassium element is preferable. In the present invention, it is particularly preferable that the alkali metal element contains at least potassium element. In addition, the molar ratio of potassium element to alkali metal element contained in the alkali metal element in the aqueous reaction precursor is preferably 0.01 or more and 1 or less, more preferably 0.1 or more and 0.5 or less.

[0018] <Source of alkaline earth metal elements> In the manufacturing method of the present invention, in addition to the alkali metal, an alkaline earth metal element may be further mixed in. Examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. As the raw material of the alkaline earth metal element, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, etc., and organic acid salts such as acetates, oxalates, citrates, etc., of the above-mentioned alkaline earth metal atoms can be used. The alkaline earth metal element raw materials may be used alone or in any combination of two or more kinds in any ratio.

[0019] (Mixing amount of alkali metal element source and alkaline earth metal element source) The ratio of the Si element source to the alkali metal element source and the alkaline earth metal element source contained in the aqueous reactant precursor is M to oxide of the Si element source. (2 / n)Molar ratio of O (M (2 / n) The molar ratio of O / SiO2 is preferably 0.02 to 0.5, where M represents an alkali metal element or an alkaline earth metal element, and n is 1 for an alkali metal and 2 for an alkaline earth metal. That is, the total amount of the alkali metal source and the alkaline earth metal source (hereinafter sometimes referred to as "alkali") is preferably 0.02 or more and 0.5 or less in terms of the molar ratio to the oxide of the Si element source. When the amount of alkali is within the above range, the target zeolite is easily obtained. From the above viewpoint, the amount of alkali is more preferably in the range of 0.05 to 0.4.

[0020] <Organic structure directing agent> In the present invention, an organic structure directing agent (OSDA) may be added to the zeolite synthesis raw material before stirring. The timing of mixing may be any time before the hydrothermal synthesis step, and the organic structure directing agent may be added at least in any stage of the mixing step, the aging step, between the mixing step and the aging step, and after the aging step and before the hydrothermal synthesis step. For example, it may be a mixing step for obtaining an aqueous reactant precursor. Specifically, the OSDA may be mixed with a Si element source, an Al element source, an alkali metal element source, and water in the synthesis raw material of the zeolite. In addition, it may be added before or after the aging step described below, or during the aging step, as long as it is before the hydrothermal synthesis step. That is, when preparing a mixed raw material for obtaining an aqueous reactant precursor (before stirring to obtain an aqueous reactant precursor, hereinafter, the raw material may be referred to as a "mixed raw material"), the organic structure-directing agent may not be added, may be added in portions, or may be added all at once. The timing of addition of the organic structure-directing agent is not particularly limited, and the organic structure-directing agent may be added during preparation of the mixed raw material, before aging, or immediately before hydrothermal synthesis. When preparing the mixed raw material, the organic structure-directing agent is preferably contained in an alkaline liquid containing an alkali metal element source (e.g., an aqueous solution containing an alkali metal element source). The organic structure-directing agent may also be added in portions at different times. The amount of OSDA mixed is preferably 0.01 or more and 1 or less in molar ratio to the Si atoms contained in the gel mixture before hydrothermal synthesis. Since the organic structure directing agent is expensive among the synthesis raw materials, it is preferable to reduce the amount used. On the other hand, from the viewpoint of obtaining a high purity target zeolite, it is preferable to contain a certain amount or more of the organic structure directing agent. From the above viewpoint, that is, from the viewpoint of being able to obtain a high purity target zeolite while being inexpensive, the content of the organic structure directing agent is more preferably 0.02 or more in molar ratio to the Si atoms, even more preferably 0.05 or more, and more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.15 or less.

[0021] (Amount of water added) The aqueous reactant precursor according to the present invention contains water (HO) as an essential component. The amount of water added is usually 5 or more, preferably 7 or more, in terms of molar ratio to Si atoms contained in the aqueous reactant precursor before hydrothermal synthesis, from the viewpoint of mitigating unevenness in heat and raw materials in the reactor and creating an environment in which zeolite is easily crystallized. From the viewpoint of reducing the amount of waste liquid to be treated, improving the one-batch efficiency (amount of zeolite recovered from one tank during hydrothermal synthesis), and enabling low-cost production by shortening the synthesis time, the amount of water to be added is usually 50 or less, preferably 40 or less, more preferably 30 or less, further preferably 25 or less, and particularly preferably 20 or less, in terms of the molar ratio to the Si atoms contained in the aqueous reactant precursor before hydrothermal synthesis. Water may be added in portions or all at once.

[0022] <Seed crystal> In the production method of the present invention, seed crystals may be present in the raw material before stirring the aqueous reactant precursor. Zeolite is preferred as the type of seed crystal, and the zeolite added as seed crystals in this production method has a framework density of 14T / 1000Å. 3 Over 19T / 1000Å 3It is preferable that the zeolite has a density of 1000Å or less (hereinafter, this zeolite may be referred to as "zeolite added in the present invention"). Here, the framework density is a value described in ATLAS of zeolite framework types Sixth revised Edition, 2007, ELSEVIER by CH. Baerlocher et al., and is a value that represents the skeletal density. That is, the framework density is the value obtained by dividing the unit volume of the zeolite by 1000Å. 3 This refers to the number of T atoms (atoms other than oxygen atoms that make up the zeolite framework structure) present per unit area, and this value is determined by the structure of the zeolite. In addition, it is desirable that the seed crystals to be added have a common CBU (composite building unit) with the target zeolite. A CBU is formed by connecting TO4 units and is a structural unit of a zeolite. The seed crystals of zeolite to be added in the present invention may be one type of zeolite alone or two or more types in any ratio and combination. The seed crystals may be uncalcined products that have not been calcined after hydrothermal synthesis, calcined products that have been calcined after hydrothermal synthesis, or ion-exchanged products. Depending on the composition of the target zeolite (content and type of alkali metal atoms, content of H2O), the synthesis environment (temperature, pH of the slurry), and other conditions, it is preferable to use uncalcined products under conditions in which uncalcined products are easily dissolved.

[0023] The amount of seed crystals added is preferably 1% by mass or more relative to SiO2 when all of the Si atoms contained in the raw material before the hydrothermal synthesis are SiO2, and in order to promote crystallization, it is preferably 2% by mass or more, particularly preferably 3% by mass or more, and most preferably 5% by mass or more. The seed crystals are synthesized zeolite, and from the viewpoint of reducing production costs, it is preferably 20% by mass or less, particularly preferably 10% by mass or less.

[0024] <Method of preparing aqueous reactant precursor> The aqueous reactant precursor of the target zeolite according to the present invention can be prepared by adding an organic structure directing agent, etc., as necessary, to the aqueous reactant precursor obtained in the mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water in a stirring tank using a stirring blade having the above-mentioned peripheral speed. The production method of the present invention is a zeolite production method that includes an aging step and a hydrothermal synthesis step of the aqueous reactant precursor prepared by the above-mentioned method in a stirring tank type reactor, for example, as shown in the schematic diagram of Figure 1.

[0025] When preparing the aqueous reactant precursor, the order of adding each raw material is not particularly limited. From the viewpoint of easy control of viscosity change during mixing, however, it is preferable to add water containing an alkali metal element source (hereinafter, sometimes referred to as "alkaline solution") to the Si element source and the Al element source.

[0026] (Mixing process) The above-mentioned Si element source, Al element source, alkali metal element source, and water are put into the stirring tank. As described above, an organic structure directing agent may be further added at this time. The mixing is performed using stirring with a stirring blade. The blade shape is not particularly limited, but the average peripheral speed at the blade tip of the stirring system is 5 m / s or more, more preferably 7 m / s or more, and particularly preferably 10 m / s or more. This is because it is important to obtain high-purity and high-crystalline zeolite, rather than simply stirring for a long time. On the other hand, in order to reduce the load on the driving part of the system and to suppress liquid splashing, it is preferable that the peripheral speed at the blade tip is 30 m / s or less, more preferably 27 m / s or less, and particularly preferably 25 m / s or less. In the present invention, it is preferable that there is a time during stirring when the peripheral speed at the blade tip becomes 10 m / s or more.

[0027] (mixing time) The mixing time is not particularly limited, but from the viewpoint of purity and uniformity, a long mixing time is preferable. On the other hand, from the viewpoint of production efficiency, a short mixing time is preferable. Therefore, the mixing time is preferably 30 seconds or more, and particularly preferably 60 seconds or more. On the other hand, it is preferably 900 seconds or less, more preferably 720 seconds or less, and particularly preferably 600 seconds or less. In particular, it is preferable that the time during which the peripheral speed at the tip of the blade becomes 10 m / s or more is within the above-mentioned range.

[0028] The peripheral speed can be calculated by the following procedure. Circumferential speed (m / s) = π × diameter of impeller (m) × (rotation speed) × (1 / 60) The peripheral speed does not necessarily have to be constant, and may change continuously. In such a case, when a constant mixing time a is given under a certain peripheral speed A, and then mixing is performed for a constant mixing time b under a peripheral speed B, the peripheral speed calculated by the following formula is defined as the average peripheral speed. In other words, the average peripheral speed is the product of the peripheral speed and the mixing time at each peripheral speed divided by the total mixing time. Average peripheral speed (m / s) = (peripheral speed A × a + peripheral speed B × b + ··· + peripheral speed N × n) / total mixing time (a + b + ··· + n) In the present invention, since stirring may be continued in the next aging step to prevent settling and to mix more uniformly, the time during which stirring is continued within the above-mentioned preferred mixing time range, for example, a peripheral speed of 5 m / s or more, more preferably 10 m / s or more, in a state containing a Si element source, an Al element source, an alkali metal element source, and water, may be regarded as the mixing step. In this case, the average peripheral speed is 5 m / s or more, since it is the portion where mixing is performed at a peripheral speed of 5 m / s or more, the average peripheral speed is 5 m / s or more.

[0029] Incidentally, elemental analysis of Si, Al, alkali metals, etc. in the aqueous mixture precursor can be carried out by filtering the aqueous mixture precursor, separating solid matter, washing, drying, and then carrying out ICP analysis.

[0030] <Aging process> In the production method of the present invention, the aqueous reactant precursor obtained by stirring at a high peripheral speed as described above is subjected to an aging step. (Aging process conditions) The temperature during the aging step is not particularly specified, but in order to avoid the generation of a poorly soluble crystalline precursor, the aqueous reactant precursor is aged at a temperature of preferably 140° C. or less, more preferably 120° C. or less, and particularly preferably 100° C. or less. The temperature may be constant during the aging, or may be changed stepwise or continuously.

[0031] (Aging time) The maturation time is not particularly limited. From the viewpoint of production efficiency, a short time is preferable, but from the viewpoint of purity and uniformity, it is preferable to carry out the maturation for a long time. Specifically, the maturation time is preferably 15 minutes or more, more preferably 30 minutes or more, and particularly preferably 60 minutes or more. On the other hand, it is preferably 36 hours or less, more preferably 24 hours or less, and particularly preferably 12 hours or less. The maturation is preferably carried out without applying external pressure because the apparatus required is simple. In addition, the maturation is preferably performed with stirring, since the raw materials are easily homogenized. The stirring method is not particularly limited. During maturation, a part or all of the remaining raw materials (e.g., seed crystals or OSDA) that have not yet been added may be added.

[0032] <Hydrothermal synthesis process> In this production method, after aging, any remaining raw materials (e.g., seed crystals or OSDA) that have not yet been added are added so as to obtain a predetermined raw material composition, and a hydrothermal synthesis step is performed. The target zeolite is synthesized by hydrothermal synthesis. The hydrothermal synthesis is usually performed by placing the composition after the addition of zeolite in a pressure-resistant container and maintaining a predetermined temperature under self-generated pressure, while stirring or rotating or rocking the container, or in a stationary state. The hydrothermal synthesis is usually performed at 140°C or higher. The hydrothermal synthesis is usually performed at 220°C or lower, preferably 200°C or lower, and more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and particularly preferably 12 hours or more, while it is usually 14 days or less, preferably 7 days or less, more preferably 5 days or less, and even more preferably 2 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. The stirring speed may be constant during the reaction, or may be changed stepwise or continuously. By carrying out the hydrothermal synthesis under the above conditions, the yield of the target zeolite is improved, impurities are less likely to be produced, and the production costs can be reduced, which is preferable.

[0033] (Zeolite Recovery) After hydrothermal synthesis, the zeolite is separated from the composition after hydrothermal synthesis (hydrothermal synthesis reaction liquid). The obtained zeolite usually contains alkali metal atoms in the pores. Furthermore, when an organic structure-directing agent is used, the zeolite usually contains the organic structure-directing agent in the pores. Hereinafter, the substances contained in the pores of the zeolite after hydrothermal synthesis, such as the organic structure-directing agent or alkali metal, may be referred to as "structure-directing agent, etc.", and the zeolite containing this in the pores may be referred to as "SDA, etc.-containing zeolite." The method for separating the SDA-containing zeolite from the hydrothermal synthesis reaction liquid is not particularly limited, but typically includes filtration, decantation, direct drying, and the like.

[0034] The SDA-containing zeolite separated and recovered from the hydrothermal synthesis reaction liquid is washed with water, dried, and then calcined or otherwise treated to remove the structure-directing agent, etc., used during the production.

[0035] The method of removing the structure-directing agent from the zeolite containing SDA or the like can be a liquid phase treatment using an acidic solution or a chemical solution containing a structure-directing agent decomposing component, an ion exchange treatment using a resin or the like, or a thermal decomposition treatment, or these treatments may be used in combination. The organic structure-directing agent contained in the zeolite can be removed by a method such as extraction with an organic solvent such as an ethanol aqueous solution. On the other hand, from the viewpoint of productivity, the organic structure-directing agent is preferably removed by firing. Usually, the zeolite is fired at a temperature of 300 to 1000°C in air or an oxygen-containing inert gas, or in an inert gas atmosphere. The firing temperature is preferably 400°C or higher, more preferably 450°C or higher, and even more preferably 500°C or higher, and is preferably 900°C or lower, more preferably 800°C or lower, and even more preferably 700°C or lower. Nitrogen or the like can be used as the inert gas.

[0036] <Zeolite produced by the production method of the present invention> The zeolite produced by the method of the present invention has a framework density of 14T / 1000Å. 3 Over 19T / 1000Å 3 The following zeolites are preferred: Such zeolites are difficult to produce in large quantities at once, and the production method of the present invention is effective for such zeolites. Moreover, the zeolite produced by the production method of the present invention is preferably a zeolite having at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. A specific example of such a zeolite is AEI zeolite.

[0037] (AEI type zeolite) The zeolite produced by the production method of the present invention includes AEI zeolite. In the present specification, AEI zeolite is taken as an example in the examples described later. Hereinafter, AEI zeolite will be described. The AEI zeolite exemplified in the examples (hereinafter, sometimes referred to as "AEI zeolite of the present invention") is a code that specifies the skeletal structure of zeolite, as defined by the International Zeolite Association (IZA), and indicates an AEI structure. The structure is characterized by X-ray diffraction data. However, when actually measuring a produced zeolite, the intensity ratio and peak position of each peak are affected by the crystal face growth direction of the zeolite, the ratio of constituent elements, adsorbed substances, the presence of defects, etc., and therefore the values ​​obtained are not exactly the same as the parameters of the AEI structure specified by the IZA, and a margin of about 10% is allowed. Major peaks observed in X-ray diffraction of AEI zeolite include, for example, the 110 plane peak at 2θ=9.5°±0.2°, the 022 plane peak at 16.9°±0.2°, and the 310 plane peak at 20.6°±0.2° when CuKα radiation is used as the radiation source.

[0038] This production method makes it possible to produce high-purity AEI zeolite on a large scale while reducing the amount of expensive organic structure-directing agents used.

[0039] As the purity of the target AEI zeolite increases, the performance such as catalytic activity when used as a catalyst improves. Therefore, the purity of the target AEI zeolite is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. The higher the purity of the target zeolite, the better, and the upper limit is 100%.

[0040] The purity of AEI zeolite can be calculated by the following procedure. First, the by-product content in the zeolite is calculated. The by-product content can be calculated from the following formula (1) using an XRD pattern obtained by XRD measurement using CuKα radiation as a radiation source. By-product content (%) = I (peak intensity of by-product) / I (peak intensity of AEI zeolite + by-product) × 100 (1)

[0041] In the above formula (1), I(AEI) is the intensity of the main peak of AEI. The main peak is the most intense peak among the XRD peaks that characterize each zeolite, and in the case of AEI zeolite, it is typically the peak at 2θ=9.5°±0.2°. I(by-product) is the intensity of the main peak of the by-product. I(by-product) is the intensity of the XRD peak that characterizes the structure of the by-product. For example, as shown in FIG. 2, when the by-product zeolite is a MOR type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=6.5±0.1°. When the by-product zeolite is a GME type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=7.5±0.1°. When the by-product zeolite is a MER type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=12.5±0.1°. When the by-product zeolite is an ANA type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=15.9±0.1°. When the by-product is sanidine, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=21.7±0.1°. When there are two or more by-products, I(by-product) is calculated by adding the peak intensities.

[0042] From the by-product content (%) calculated as above, the purity of the AEI zeolite can be calculated from the following formula (2). Purity of AEI zeolite (%) = 100 - by-product content (%) (2)

[0043] (Applications of AEI zeolite) The use of the zeolite prepared in the present invention is not particularly limited, but it is preferably used as a catalyst, an adsorbent, a separation material, etc. Among them, it is preferable to use it as a catalyst or an adsorbent. The AEI zeolite of the embodiment is particularly preferably used as a catalyst for purifying exhaust gases of automobiles, etc. In addition, the AEI zeolite is also preferably used as an adsorbent for purifying exhaust gases of automobiles, etc. EXAMPLES

[0044] Hereinafter, the present invention will be specifically described by way of examples. However, the present invention is not limited to the following examples insofar as it does not exceed the gist thereof.

[0045] [Analysis and Evaluation] The analysis of the zeolites obtained in the following examples and comparative examples was carried out by the following method. [Measurement of Powder XRD] (Sample Preparation) 100 mg of a zeolite sample manually pulverized using an agate mortar was set in a sample holder of the same shape so as to have a constant sample amount. (Apparatus Specifications and Measurement Conditions) The specifications and measurement conditions of the powder XRD measuring apparatus are as follows.

[0046] [Table 1]

[0047] (Purity of AEI-Type Zeolite) In the XRD pattern obtained by XRD measurement, the purity of the AEI-type zeolite was determined by the aforementioned formulas (1) and (2) from the intensity of the main peak of the AEI-type zeolite and the intensity of the main peak of each by-product. Since there was a measurement background, when the peak intensity was 40 or less, it was defined as the background and denoted as "-".

[0048] [Measurement of ICP] (ICP Apparatus) ICP-OES apparatus: Thermo Fisher Scientific, iCAP7600Duo. was used. (Sample Preparation) The aqueous reaction precursor was obtained through the processes of filtration, washing, and drying, and about 10 mg of the recovered solid (hereinafter, sometimes referred to as the precursor solid obtained through this process) was set in a sample holder dedicated for measurement. (Apparatus Specifications and Measurement Conditions) The recovered solid was dissolved by heating in an aqueous alkali solution and an aqueous hydrofluoric acid solution, and the alkali metal and Al contents were then quantified by inductively coupled plasma (ICP) emission spectrometry to determine the alkali metal / Al ratio in the solid content of the composition.

[0049] [Reference example 1] 0.34g NaOH (Wako Pure Chemicals, 97% by mass) and 0.20g KOH (Wako Pure Chemicals, 85% by mass) were added to 5.71g of water and stirred for 300 seconds to prepare an alkaline aqueous solution, after which 0.43g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, Kyoward Chemicals) was added and stirred for another 300 seconds. 4.46g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemicals) was added to prepare a white suspension. The mixture was mixed at room temperature for 2 hours under low peripheral speed conditions (average peripheral speed was 3m / s) in a 100cc scale. The solid matter of this precursor was measured by ICP, and the alkali metal atom / Al ratio in the mixture was 1.0. The prepared aqueous reactant precursor (referred to as Precursor No. 1 in Tables 9 to 11) was placed in a 100 cc autoclave and aged for 2 hours under stationary conditions at 80°C. To the aged mixture, 1.4 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA), and the mixture was stirred for 300 seconds (s), after which 0.13 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 SiO2 / Al2O3 (SAR = 23) were mixed and stirred at room temperature for 30 min to obtain a pre-reaction mixture. The molar composition ratio of the pre-reaction mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0050] This pre-reaction mixture was placed in a 100 cc autoclave and hydrothermal synthesis was carried out for 24 hours while stirring (15 rpm) the entire container at a temperature of 180°C. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 1 was measured, an XRD pattern was shown with peaks and relative intensities at the positions shown in Table 2 in lattice spacing representation, confirming the synthesis of AEI type zeolite. The proportion of AEI type zeolite in powder 1 was 100%.

[0051] [Table 2]

[0052] [Reference example 2] 38 g of amorphous Al(OH)3 (Al2O3, 53.5 mass%, Kyoward Chemical) was added to 300 g of water, and 394 g of colloidal silica SiO2 (SiO2, 40.2 mass%, Nissan Chemical) was added to prepare a slurry A-1 solution. 30 g of NaOH (Wako Pure Chemical, 97 mass%), 18 g of KOH (Wako Pure Chemical, 85 mass%), and 177 g of water were mixed and stirred to dissolve, preparing a transparent solution B-1. The transparent solution B-1 was added to the slurry A-1, and mixed at room temperature for 3 min in a 2L scale mixer (average peripheral speed 23 m / s), to prepare an aqueous reactant precursor (referred to as precursor No. 2 in Tables 9 to 11). As a result of ICP measurement of the solid matter of this precursor, the alkali metal atom / Al in the mixture was 1.0. 0.95 kg of the prepared aqueous reactant precursor was placed in a 2 L-scale stirred tank reactor, and then aged at 80°C for 4 hours while stirring at 240 rpm using a Fullzone impeller (3 baffles). To the aged mixture, 119 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA). Finally, 11.9 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3The mixture was stirred at room temperature for 30 min to obtain a pre-reaction mixture. The molar composition ratio of the pre-reaction mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0053] This pre-reaction mixture was stirred (360 rpm) at a temperature of 180 ° C. for 15 hours to carry out hydrothermal synthesis. At this time, a full zone blade was used in the stirring tank type reactor, and three baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 2 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 3 in lattice spacing was observed, and it was confirmed that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 2 was 96.5%. The XRD pattern of this powder 2 is shown in Figure 3. In Figure 3, the vertical axis is intensity (cps) and the horizontal axis is diffraction angle 2θ (°).

[0054] [Table 3]

[0055] [Reference example 3] 40.4 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 300 g of water, and 416.4 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-2 solution. 31.8 g of NaOH (manufactured by Wako Pure Chemical Industries, 97% by mass), 18.5 g of KOH (manufactured by Wako Pure Chemical Industries, 85% by mass), and 140 g of water were mixed and stirred to dissolve, preparing a transparent solution B-2. The transparent solution B-2 was added to the slurry A-2 and mixed for 1.5 min at room temperature using a 2 L scale mixer (average peripheral speed 21 m / s). The same procedure was repeated a total of 44 times, and these were combined to prepare an aqueous reactant precursor (referred to as Precursor No. 3 in Tables 9 to 11). The solid matter of this precursor was measured by ICP, and the ratio of alkali metal atoms / Al in the mixture was 1.1. 39.78 kg of the prepared aqueous reactant precursor was placed in a 100 L scale stirred tank reactor, and then aged at 80°C for 6 hours while stirring at 120 rpm using a Max Blend blade (two baffles). After aging, 5.3 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to the mixture after aging, and then 1.5 kg of water was sprinkled on it for washing. Finally, 0.7 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The mixture was stirred at room temperature for 30 minutes to obtain a pre-reaction mixture. The molar composition ratio of the raw material mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0056] This pre-reaction mixture was stirred (80 rpm) at a temperature of 180°C and hydrothermal synthesis was carried out for 16 hours. At this time, a Max Blend blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 3 was measured, an XRD pattern with peaks and relative intensities at the positions shown in Table 4 in lattice spacing was observed, and it was confirmed that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 3 was 93.4%.

[0057] [Table 4]

[0058] [Example 1] 343g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 2550g of water, and 3539g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-3 solution. 270g of NaOH (manufactured by Wako Pure Chemical Industries, 97% by mass), 157g of KOH (manufactured by Wako Pure Chemical Industries, 85% by mass), and 1190g of water were mixed and stirred to dissolve, preparing a transparent solution B-3. The transparent solution B-3 was added to the slurry A-3, and mixed at room temperature for 720s using a high peripheral speed stirrer (average peripheral speed of the blade tip was 11m / s) with a 20L scale stirring tank. The solid matter of this precursor was measured by ICP, and the alkali metal atom / Al in the mixture was 0.9. The prepared aqueous reactant precursor (referred to as precursor No. 4 in Tables 9 to 11) was placed in a stirred tank reactor and aged for 6 hours while stirring (240 rpm) at 80°C. To the aged mixture, 122 g of a 20% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA), and the mixture was stirred for 5 minutes. After that, 12.2 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The mixture was stirred at room temperature for 30 min to obtain a pre-reaction mixture. The molar composition ratio of the pre-reaction mixture other than the seed crystals is shown below. SiO2:0.08Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0059] This pre-reaction mixture was placed in a 2L-scale stirred tank reactor and hydrothermal synthesis was carried out for 10 hours while stirring (360 rpm) at a temperature of 180 ° C. At this time, a full zone impeller and three baffles were used in the stirred tank reactor. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C. for 12 hours. When the XRD of the obtained powder 4 was measured, it was confirmed that the lattice spacing had peaks and relative intensities at the positions shown in Table 5, and that AEI-type zeolite was synthesized. The XRD pattern of this powder 4 is shown in Figure 4. In Figure 4, the vertical axis is intensity (cps) and the horizontal axis is diffraction angle 2θ (°). The proportion of AEI-type zeolite in powder 4 was 100%.

[0060] [Table 5]

[0061] [Examples 2 and 3] In Examples 2 and 3, the composition before hydrothermal synthesis was the same as in Example 1 (SiO2: 0.08Al2O3: 0.3NaOH: 0.1KOH: 17.5H2O: 0.1OSDA), and zeolite synthesis was performed in the same manner as in Example 1, except that the preparation scale of the aqueous reactant precursor, the peripheral speed of the stirrer used, the aging of the gel, the hydrothermal synthesis conditions and the stirring method were changed as shown in Tables 9, 10, 11 and 12. The prepared aqueous reactant precursors are referred to as Precursor No. 5 and 6 in Tables 9 to 11, respectively. In Examples 2 and 3, the precursors (alkali metal / Al=0.9 or 1.0) were produced using a high-speed stirrer (average peripheral speed at the blade tip of 10 m / s or more), and it was confirmed that they contained high-purity (95% or more) AEI zeolite regardless of the aging, hydrothermal synthesis conditions, or amount of the material. The XRD pattern of Example 3 is shown in Figure 3.

[0062] [Example 4] 3474.4 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 25800 g of water, and 35810.4 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added to prepare a slurry A-4 solution. 2734.8 g of NaOH (manufactured by Wako Pure Chemical Industries, Ltd.), 1589.3 g of KOH (manufactured by Wako Pure Chemical Industries, Ltd.), and 12040 g of water were mixed and stirred to dissolve, preparing a transparent solution B-4. The transparent solution B-4 was added to the slurry A-4, and mixed at room temperature for 12 min using a 150 L scale high peripheral speed stirrer (average peripheral speed of the stirring blade was 11 m / s). The same gel mixing process was repeated a total of 23 times. 1555.7 kg of the prepared aqueous reactant precursor (referred to as precursor No. 7 in Tables 9 to 12) was placed in a 2000 L-scale stirred tank reactor, and then aged at 80°C for 6 hours while stirring at 30 rpm using a Supermix blade (two baffles) ("MR205" manufactured by Satake Multimix Co., Ltd.). After the aging, 208.1 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA), and then 40 kg of water was sprinkled on the mixture for washing. Finally, 27.6 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 The raw gel mixture was obtained by mixing SiO2 / Al2O3 (SAR = 23) in 50 kg of water and stirring for 30 min at room temperature. The molar composition ratio of the raw material gel mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0063] This raw gel mixture was stirred (45 rpm) at a temperature of 180°C and hydrothermal synthesis was carried out for 22 hours. At this time, a Supermix blade was used in the stirring tank type reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours. When the XRD of the obtained powder 5 was measured, it was confirmed that the lattice spacing had peaks and relative intensities at the positions shown in Table 6, and that AEI type zeolite was synthesized. The proportion of AEI type zeolite in powder 5 was 100%.

[0064] [Table 6]

[0065] [Comparative Example 1] 380g of water, 43.3g of amorphous Al(OH)3 (Al2O3 53.5% by mass, Kyoward Chemical Co., Ltd.) were added, 309g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Co., Ltd.) was added, and 135.7g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide 20% aqueous solution (Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to prepare a slurry A-5 solution. 46.4g of NaOH (Wako Pure Chemical Industries, Ltd., 97% by mass) was dissolved in 134g of water to prepare a transparent solution B-5. The transparent solution B-5 was slowly lowered (0.5cc / min) into the slurry A-5, and while adding the alkaline aqueous solution, it was mixed at room temperature for 3600s with a 2L scale low peripheral speed agitator (average peripheral speed at the blade tip was 2m / s). The aqueous reactant precursor obtained (referred to as precursor No. 8 in Tables 9 to 11) was placed in a stirred tank reactor and aged for 2 hours while stirring (450 rpm) at room temperature. ICP measurement of the solid matter of this precursor revealed that the ratio of alkali metal atoms / Al in the mixture was 2.2. After aging, 9.0 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000 Å) was added as seed crystals to the mixture. 3SiO2 / Al2O3 (SAR) (SAR) = 23) was swollen in 30 g of water, mixed, and stirred at room temperature for 60 min to obtain a pre-reaction mixture. The molar composition ratio of the pre-reaction mixture other than the seed crystals is shown below. SiO2:0.08Al2O3:0.4NaOH:17.5H2O:0.1OSDA

[0066] This pre-reaction mixture was placed in a 2L-scale stirred tank reactor and hydrothermal synthesis was carried out for 24 hours while stirring at 180 ° C (240 rpm). At this time, a full zone impeller and three baffles were used in the stirred tank reactor. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C for 12 hours. When the XRD of the obtained powder was measured, it was found to be an AEI type powder containing impurities that showed an XRD pattern with peaks and relative intensities at the positions shown in Table 7 in lattice spacing representation. The proportion of AEI type zeolite in the powder was 74%, and it was confirmed that impurities were mixed in at a high proportion. The XRD pattern of this powder is shown in Figure 3.

[0067] [Table 7]

[0068] [Comparative Example 2] 16620g of water was added to 3430g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, Kyoward Chemical Co., Ltd.), 24380g of colloidal silica SiO2 (SiO2, 40.2% by mass, Nissan Chemical Co., Ltd.), and 10860g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide 20% aqueous solution (Seichem Co., Ltd.) was added as an organic structure directing agent (OSDA) to prepare a slurry A-6 solution. 10440g of NaOH (25% aqueous solution, Wako Pure Chemical Industries, Ltd.) and 1570g of KOH (Wako Pure Chemical Industries, 85% by mass) were mixed and stirred to dissolve, preparing a transparent solution B-6. The transparent solution B-6 was added to the slurry A-6 and mixed for 10800s at room temperature using a 100L scale low peripheral speed agitator (average peripheral speed of the blade tip was 2m / s). Thereafter, 10,440 g of demineralized water and the remaining 1,084 g of colloidal silica SiO2 (SiO2, 40.2 mass%, Nissan Chemical Co., Ltd.) were added, and then 10,440 g of demineralized water was added, followed by aging for 3,600 s. The solid matter of this precursor (referred to as Precursor No. 9 in Tables 9 to 11) was subjected to ICP measurement, and the ratio of alkali metal atoms / Al in the mixture was found to be 1.9. The prepared aqueous reactant precursor was placed in a stirred tank reactor and aged for 8 hours while stirring (80 rpm) at 80°C. After aging, 710 g of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000 Å) was added as seed crystals to the mixture. 3 The mixture was stirred at room temperature for 60 minutes to obtain a pre-reaction mixture. The molar composition ratio of the pre-reaction mixture other than the seed crystals is shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0069] This pre-reaction mixture was placed in a 100L-scale stirred tank reactor and hydrothermal synthesis was carried out for 24 hours while stirring (80 rpm) at 170 ° C. At this time, a paddle blade and two baffles were used in the stirred tank reactor. After the hydrothermal synthesis reaction, the reaction liquid was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100 ° C for 12 hours. When the XRD of the obtained powder was measured, it was found to be an AEI type powder containing impurities that showed an XRD pattern with peaks and relative intensities at the positions shown in Table 8 in lattice spacing. The proportion of AEI type zeolite in the powder was 73%, and it was confirmed that impurities were mixed in at a high proportion. The XRD pattern of this powder is shown in Figure 3.

[0070] [Table 8]

[0071] For Reference Examples 1 to 3, Examples 1 to 4, and Comparative Examples 1 and 2, the preparation conditions (mixing and aging conditions) of the aqueous reactant precursors are summarized in Tables 9 and 10, and the stirring conditions and hydrothermal synthesis conditions are summarized in Table 11. Moreover, the evaluation results for the Reference Example, each Example, and Comparative Example are shown in Table 12.

[0072] [Table 9]

[0073] [Table 10]

[0074] [Table 11]

[0075] [Table 12]

[0076] In the small-scale laboratory synthesis of Reference Example 1, despite the low peripheral speed (3 m / s) rotation, a precursor with alkali metal (Na+K) / Al=1.0 was formed, and hydrothermal synthesis was obtained under aging and tumbling conditions to obtain high-purity AEI. On the other hand, from the results of using 100 L stirring in Comparative Example 2 in addition to 1 L in Comparative Example 1, it can be inferred that a high molar ratio of alkali metals is shown relative to the Al element source in the raw aqueous reactant prepared under low average peripheral speed conditions, and that alkali metals are localized. It was found that when this non-uniform precursor gel is aged and further hydrothermally synthesized, a large amount of impurities are generated. In other words, even if the target zeolite can be easily produced under low peripheral speed conditions on a small scale, it is difficult to produce a high-purity target product in a mass-production scale stirred tank reactor. However, by using the aqueous mixture precursor prepared in the high peripheral speed stirrer of the present invention (average peripheral speed of 5 m / s or more), maturing and further hydrothermal synthesis, it is possible to obtain a target zeolite of high purity at any synthesis scale. In addition, from the characteristic that the molar ratio of the alkali metal to the Al element source contained in the raw aqueous reactant is 0.8 to 1.2, it can be inferred that an aqueous mixture precursor having uniformity equivalent to that of a precursor prepared on a lab scale was prepared under high peripheral speed conditions. [Industrial Applicability]

[0077] According to the production method of the present invention, a uniform aqueous reactant precursor can be prepared in a short time even on a large scale, and a high-purity, high-crystalline zeolite can be obtained in large quantities by aging and hydrothermal synthesis of the precursor. Zeolites can be used as various materials, and are widely used, for example, as adsorbents, ion exchange agents, industrial catalysts, and environmental catalysts. The method of the present invention, which can efficiently produce such zeolites, is an industrially important technology and can contribute to industry.

Claims

1. A method for producing a zeolite, comprising: a mixing step of mixing at least a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; an aging step of aging the aqueous reactant precursor after the mixing step; and a hydrothermal synthesis step, A method for producing a zeolite, wherein in the mixing step, the aqueous reactant precursor is mixed using a stirring tank of 10 liters or more and a stirring blade, and in the mixing step, an average peripheral speed of the blade tip is 5 m / s or more.

2. The method for producing a zeolite according to claim 1, wherein the total time during which the blade tip peripheral speed is 10 m / s or more is 30 s or more and 900 s or less.

3. The method for producing a zeolite according to claim 1, wherein an organic structure-directing agent is added at least in any one of the stages of the mixing step, the aging step, between the mixing step and the aging step, and after the aging step and before the hydrothermal synthesis step.

4. The method for producing a zeolite according to claim 1 , wherein the mixing step, the aging step, and the hydrothermal synthesis step are carried out in a stirred tank reactor.

5. The framework density of the zeolite is 14T / 1000Å. 3 Over 19T / 1000Å 3 The method for producing the zeolite according to claim 1, wherein:

6. The method for producing a zeolite according to claim 1, wherein the zeolite has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring.

7. The ratio of elemental Si to elemental Al in the aqueous reactant precursor is a molar ratio of oxide of elemental Si to oxide of elemental Al (SiO 2 / Al 2 O 3 The method for producing a zeolite according to claim 1, wherein the molar ratio of the zeolite to the zeolite is 5 or more and 1,000 or less.

8. The ratio of elemental Si and alkali metal contained in the aqueous reactant precursor is M to oxide of elemental Si. (2 / n) O (M represents an alkali metal element, and n is 1) molar ratio (M (2 / n) O / SiO 2 The method for producing a zeolite according to claim 1, wherein the molar ratio of the zeolite to the zeolite is 0.01 or more and 0.5 or less.

9. The method for producing a zeolite according to claim 1 , wherein an alkaline earth metal element source is further mixed in the mixing step.

10. The ratio of elemental Si to alkali metal and alkaline earth metal elements contained in the aqueous reactant precursor is M to oxide of elemental Si. (2 / n) O (M represents an alkali metal element and an alkaline earth metal element, n is 1 for an alkali metal and 2 for an alkaline earth metal) molar ratio (M (2 / n) O / SiO 2 The method for producing a zeolite according to claim 9, wherein the molar ratio of the zeolite to the zeolite is 0.02 or more and 0.5 or less.

11. The method for producing a zeolite according to claim 1 , wherein the alkali metal element source comprises at least a potassium element source.

12. The method for producing a zeolite according to claim 11, wherein a molar ratio of potassium element to alkali metal element contained in the alkali metal element source in the aqueous reactant precursor is 0.01 or more and 1 or less.

Citation Information

Patent Citations

  • AEI zeolite and manufacturing method and application thereof

    JP2017081809A

  • Method for producing AEI type zeolite

    JP2017206417A

  • Production method of AEI zeolite, catalyst, and adsorbent

    JP2021147260A